The Effect of Acupunture Provision on Breast Milk Production - Arifah Nur Chasanah; Machfudloh Machfudloh; Isna Hudaya (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Breastfeeding is an adaptation process experienced by postpartum mothers. If a mother has a good milk production while breastfeeding, the mother will succeed for exclusive breastfeeding. Acupuncture is one of the best solutions to the problem of the smooth production of breast milk. This therapy can maximize the stimulation of the hormone prolactin milk production. Objective: to analyze the effect of acupuncture on breast milk production in postpartum mothers. Method: in this study was a Pre-Experimental Design Experiment with Pretest Postest Control Group Design. Sampling in this study used purposive sampling with a total sample of 10 respondents, 5 respondents for the interval group and 5 respondents for the control group. The instrument used was a questionnaire. The statistical test used is Mann-Whitney. Results: this study showed that there was an effect of acupuncture on milk production (p = 0.004). Acupuncture has an influence on increasing postpartum breast milk production.